A Case of 47, XXX Presenting as Secondary Amenorrhea - Harpreet Kaur (Fertility & Reproduction, 2022)
Objective: 47,XXX is a form of sex chromosome anomaly with an extra copy of X chromosome. It can have a varying presentation ranging from a few physical characteristics to intellectual and learning disabilities to primary ovarian insufficiency (POI). Although for most triple X syndrome patients, sexual development and fertility are normal, a few may present with amenorrhea and POI. We are presenting a case of triple X patient who presented with POI at 23 years of age. The relatively rare occurrence of this entity prompted us to report this case. Case Presentation: Index case was presented to us at 23 years of age with secondary amenorrhea and desire for conception. Secondary sex characteristics were normal except for axillary hair that was scanty. Workup revealed a 47, XXX karyotype and a diagnosis of POI was made. We are presenting this case to highlight this important entity as a differential in cases of amenorrhea and to discuss the fertility options available in such cases. Conclusion: Women with triple X syndrome have varying phenotypic presentations. Those presenting with POI will need hormone replacement therapy, psychological support and counselling for fertility options.